Factors affecting production of beta-carotene from Dunaliella salina microalgae. (October 2020) - Pourkarimi, Sara; Hallajisani, Ahmad; Alizadehdakhel, Asghar; Nouralishahi, Amideddin; Golzary, Abooali
Abstract: Dunaliella Salina is a carotene-producing microalgae well-known for its superb ability to accumulate valuable beta-carotene. The factors affecting the bio-beta-carotene production from Dunaliella salina microalgae have been investigated in this study. First, the different usages of Dunaliella salina, especially for the production of beta-carotene, are described. Then, the factors affecting the process of obtaining beta-carotene from Dunaliella salina in the culture system, culture conditions, and downstream processes are investigated. Investigations show that application of airborne photo-bioreactor culture system improves the mechanism of production. It was found that among the culture conditions, the parameters such as ambient salinity, temperature, and intensity of illumination are the most effective ones. The optimal values for these parameters, the highest cellular density of Dunaliella salina and the highest beta-carotene production are determined. The extraction step is known as the most critical step in the downstream processes of beta-carotene production. Graphical abstract: Image 1 Highlights: Among the downstream processes, extraction step has the highest technical and economic importance. The most suitable method for the extraction of beta-carotene is the use of a combination of solvents. It has been shown that among the combined solvents, CH2 Cl2 -decane has the best performance. Various factors affect the production of beta-carotene from Dunaliella salina microalgae, including type of culture systems, adjustment of culture conditions considering nutritional and environmental factors, and downstream processes such as beta-carotene extraction.